2013
DOI: 10.1007/s11999-012-2639-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraprosthetic Dislocation: A Specific Complication of the Dual-mobility System

Abstract: Background The dual-mobility concept was proposed as an alternative to prevent postoperative dislocation events. However, intraprosthetic dislocation (IPD) is a troublesome and specific complication induced by the loss of the polyethylene retentive rim and escape of the femoral head from the polyethylene liner. The factors associated with IPD are unknown as only isolated cases have been reported and do not provide a clear understanding of the mechanisms of failure.Questions/purposes We therefore (1) identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
153
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(158 citation statements)
references
References 16 publications
1
153
2
2
Order By: Relevance
“…Mohammed et al [19] have reported severe metallosis after IPD in their case of a primary THA performed with a dual-mobility cup. Several other case reports have also demonstrated the potential complications of these designs [1,2,14,16,18,19,21,23]. Further studies detail this important complication of dualmobility articulations.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Mohammed et al [19] have reported severe metallosis after IPD in their case of a primary THA performed with a dual-mobility cup. Several other case reports have also demonstrated the potential complications of these designs [1,2,14,16,18,19,21,23]. Further studies detail this important complication of dualmobility articulations.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, we similarly evaluated a dualmobility articulation; however, it is different in design from most of the aforementioned studies. Although there are advantages to dual-mobility implants, they are not without disadvantages such as polyethylene wear, loosening, and the unique complication of IPD [1,2,14,16,18,19,21,23]. We therefore asked: (1) What is the cup survivorship when the dual-mobility articulation is used in the setting of primary THA?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Philippot et al recently postulated three mechanisms of intraprosthetic dislocation after analysis of 81 such cases from a series of 1960 primary dual-mobility THAs implanted between 1985 and 1998 [13]. Type I "pure" dislocation results from wear of the polyethylene retentive rim in an otherwise functional prosthesis; this accounted for 32% of cases.…”
Section: Discussionmentioning
confidence: 99%